2001
DOI: 10.1021/es001979r
|View full text |Cite
|
Sign up to set email alerts
|

Biohydrogen Production as a Function of pH and Substrate Concentration

Abstract: The conversion of organics in wastewaters into hydrogen gas could serve the dual role of renewable energy production and waste reduction. The chemical energy in a sucrose rich synthetic wastewater was recovered as hydrogen gas in this study. Using fractional factorial design batch experiments, the effect of varying pH (4.5-7.5) and substrate concentration (1.5-44.8 g COD/L) and their interaction on hydrogen gas production were tested. Mixed bacterial cultures obtained from a compost pile, a potato field, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
261
4
18

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 631 publications
(313 citation statements)
references
References 12 publications
19
261
4
18
Order By: Relevance
“…For example, one study showed that both hydrogen yield and production rate increased with increasing sucrose up to moderate OLR (5 to 20 g COD/l); however both values decreased when the substrate concentration reached 30 g COD/l [78]. Similar results have been observed in other studies, although inhibition occurred at different substrate concentrations [22,83]. These results suggest that elevated substrate loadings have a toxic effect on the bacteria.…”
Section: Wastewater Substratessupporting
confidence: 70%
See 1 more Smart Citation
“…For example, one study showed that both hydrogen yield and production rate increased with increasing sucrose up to moderate OLR (5 to 20 g COD/l); however both values decreased when the substrate concentration reached 30 g COD/l [78]. Similar results have been observed in other studies, although inhibition occurred at different substrate concentrations [22,83]. These results suggest that elevated substrate loadings have a toxic effect on the bacteria.…”
Section: Wastewater Substratessupporting
confidence: 70%
“…from the genus Clostridium) generate gas in the exponential growth phase, and then the metabolism shifts from H 2 /acid production to solventogenesis when the culture reaches stationary growth phase [20,21]. Poor hydrogen yields have also been linked to high hydrogen partial pressure, high substrate concentration, low iron concentration, and/or low pH [20,22,23,24]. Current maximum hydrogen yields obtained do not make the fermentative process an attractive one from an economic point of view when compared to conventional reforming techniques.…”
Section: Microbial Processes Producing Hydrogenmentioning
confidence: 99%
“…While a conversion efficiency of 33% is theoretically possible for hydrogen production from glucose, only half of this is usually obtained under batch and continuous fermentation conditions (17)(18)(19) …”
Section: Fermenting Sugarsmentioning
confidence: 99%
“…Some studies investigated the combined effect of two variables such as pH and substrate concentrations [5,6], temperature and pressure release methods [7], and pH and sulfate concentration [8] on the biohydrogen production process. Ginkel and Sung [5] tested the effect of varying pH (4.5e7.5) and substrate concentration (1.5e44.8 g COD/L) and Abbreviations: ADM1, anaerobic digestion model No.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies investigated the combined effect of two variables such as pH and substrate concentrations [5,6], temperature and pressure release methods [7], and pH and sulfate concentration [8] on the biohydrogen production process. Ginkel and Sung [5] tested the effect of varying pH (4.5e7.5) and substrate concentration (1.5e44.8 g COD/L) and Abbreviations: ADM1, anaerobic digestion model No. 1; ADS, anaerobic digester sludge; ANN, artificial neural network; APE, average percentage error; COD, chemical oxygen demand; HRT, hydraulic retention time; MAE, mean absolute error; MSE, mean square error; UASB, upflow anaerobic sludge blanket.their interaction on hydrogen production in batch tests using compost as the seed microflora and sucrose as the substrate.…”
Section: Introductionmentioning
confidence: 99%